Microparticle alpha‐2‐macroglobulin enhances pro‐resolving responses and promotes survival in sepsis - Jesmond Dalli; Lucy V Norling; Trinidad Montero‐Melendez; Donata Federici Canova; Hazem Lashin; Anton M Pavlov; Gleb B Sukhorukov; Charles J Hinds; Mauro Perretti (EMBO Molecular Medicine, 2013)
Abstract Incorporation of locally produced signaling molecules into cell‐derived vesicles may serve as an endogenous mediator delivery system. We recently reported that levels alpha‐2‐macroglobulin (A2MG)‐containing microparticles are elevated in plasma from patients with sepsis. Herein, we investigated the immunomodulatory actions of A2MG containing microparticles during sepsis. Administration of A2MG‐enriched (A2MG‐E)‐microparticles to mice with microbial sepsis protected against hypothermia, reduced bacterial titers, elevated immunoresolvent lipid mediator levels in inflammatory exudates and reduced systemic inflammation. A2MG‐E microparticles also enhanced survival in murine sepsis, an action lost in mice transfected with siRNA for LRP1, a putative A2MG receptor. In vitro, A2MG was functionally transferred onto endothelial cell plasma membranes from microparticles, augmenting neutrophil–endothelial adhesion. A2MG also modulated human leukocyte responses: enhanced bacterial phagocytosis, reactive oxygen species production, cathelicidin release, prevented endotoxin induced CXCR2 downregulation and preserved neutrophil chemotaxis in the presence of LPS. A significant association was also found between elevated plasma levels of A2MG‐containing microparticles and survival in human sepsis patients. Taken together, these results identify A2MG enrichment in microparticles as an important host protective mechanism in sepsis.